Chiari 1 Malformation in a Child with Febrile Seizures, Parasomnias, and Sleep Apnea Syndrome - Marco Zaffanello; Francesca Darra; Tommaso Lo Barco; Francesco Sala; Emma Gasperi; Giorgio Piacentini (Case Reports in Pediatrics)
Introduction. The type I is the most common Chiari malformation in children. In this condition, the lower part of the cerebellum, but not the brain stem, extends into the foramen magnum at the base of the skull leading to disturbances in cerebrospinal fluid circulation and to direct compression of nervous tissue. Case report. We describe a 4-year-old Caucasian female child with febrile seizures, headache, parasomnias, and a delay of speech. The child underwent a magnetic resonance imaging to investigate these neurological signs, disclosing a Chiari malformation type 1. The polysomnography showed a mild-moderate sleep-disordered breathing, increased number of central sleep apneas, and generalized spike waves at sleep onset. Conclusions. Seizures have been seldom described in CM1 patients. The main reasons for performing MRI in this case were frequent seizures, a delay of speech, and headache, leading to an unexpected diagnosis of CM1. Polysomnography detected a discrete SDB.